FRACTURA RADICULAR HORIZONTAL. SEGUIMIENTO DE 22 MESES (2018)
Horizontal root fracture is associated to a low percent of all events of dental trauma that come in the dental office. But day to day, this is oppress, when it is present, the big questions are: ¿Will be successful this case? ¿What is the mental result on this patient? ¿How long will be the tooth in the mouth? Finally, after all type of efforts, the patient could loose the tooth.The purpose of this case report is to demonstrate how's a loss case, by a dental treatment with a low pronostique, was success